Country Social Analysis : Ethnicity and Development in Vietnam - Main Report - World Bank (World Bank, 2012)
This report " Country Social Analysis (CSA) " focused on ethnicity and development in Vietnam is a provocative analysis of marginality in contemporary Southeast Asia. It seeks to understand the macro social and political processes, and provides an analysis of how social, political, and cultural factors influence the opportunities and constraints to more equitable, inclusive development. This study provides research findings to support both the Bank's and the government of Vietnam's goals of social inclusion for ethnic minorities and poverty reduction. Previous studies, including the Bank's Country Partnership Study for Vietnam (CPS) and the government's Socioeconomic Development Plan (SEDP), focus on four organizing principles: (1) improving the business environment; (2) strengthening social inclusion; (3) strengthening natural resource and environmental management; and (4) improving governance. This study focuses particularly on the issue of strengthening social inclusion. Part one of this summary report is a literature review that discusses background information on ethnic minorities, including their classification, history, current living conditions, and poverty outcomes. Part two presents the results of field-based research and provides in-depth analysis of six fundamental factors that explain how differences between ethnic groups contribute to remarkably different livelihood strategies and economic outcomes. Part three summarizes the policy implications of research findings, suggesting areas for further consideration.